NFAT2 is a critical regulator of the anergic phenotype in chronic lymphocytic leukaemia - Melanie Märklin (Nature Portfolio, 2017)
NFAT2 is a transcription factor that has been linked with chronic lymphocytic leukaemia (CLL), but its functions in CLL manifestation are still unclear. Here the authors show, by analysing mouse CLL models and characterising biopsies from CLL patients, that NFAT2 is an important regulator for the anergic phenotype of CLL.